From cycloheptathiophene-3-carboxamide to oxazinone-based derivatives as allosteric HIV-1 ribonuclease H inhibitors - Serena Massari; Angela Corona; Simona Distinto; Jenny Desantis; Alessia Caredda; Stefano Sabatini; Giuseppe Manfroni; Tommaso Felicetti; Violetta Cecchetti; Christophe Pannecouque; Elias Maccioni; Enzo Tramontano; et al. (Taylor & Francis Group, 2019)
The paper focussed on a step-by-step structural modification of a cycloheptathiophene-3-carboxamide derivative recently identified by us as reverse transcriptase (RT)-associated ribonuclease H (RNase H) inhibitor. In particular, its conversion to a 2-aryl-cycloheptathienoozaxinone derivative and the successive thorough exploration of both 2-aromatic and cycloheptathieno moieties led to identify oxazinone-based compounds as new anti-RNase H chemotypes. The presence of the catechol moiety at the C-2 position of the scaffold emerged as critical to achieve potent anti-RNase H activity, which also encompassed anti-RNA dependent DNA polymerase (RDDP) activity for the tricyclic derivatives. Benzothienooxazinone derivative 22 resulted the most potent dual inhibitor exhibiting IC50s of 0.53 and 2.90 μM against the RNase H and RDDP functions. Mutagenesis and docking studies suggested that compound 22 binds two allosteric pockets within the RT, one located between the RNase H active site and the primer grip region and the other close to the DNA polymerase catalytic centre.